Meiosis in flowering plants and other green organisms - Harrison, C Jill (Journal of experimental botany, 2010)
Sexual eukaryotes generate gametes using a specialized cell division called meiosis that serves both to halve the number of chromosomes and to reshuffle genetic variation present in the parent. The nature and mechanism of the meiotic cell division in plants and its effect on genetic variation are reviewed here. As flowers are the site of meiosis and fertilization in angiosperms, meiotic control will be considered within this developmental context. Finally, we review what is known about the control of meiosis in green algae and non-flowering land plants and discuss evolutionary transitions relating to meiosis that have occurred in the lineages giving rise to the angiosperms